Adverse outcome pathways - development and potential regulatory application - Rossi Lima, Thania Rios [UNESP]; Souza, Nathalia Pereira de [UNESP]; Pereira, Lilian Cristina [UNESP]; Viana de Camargo, Joao Lauro [UNESP] (Fundacao Oswaldo Cruz, Inst Nacional Controle Qualidade & Saude, 2021)
Introduction: Over the last two decades, chemical safety assessment and regulatory toxicology have progressed from empirical science based on direct observation of apical adverse outcomes in whole organisms to a predictive practice that infers outcomes and risks on the basis of accumulated understanding of toxicological mechanisms and modes of action. Objective: To provide general concepts on how Adverse Outcome Pathways (AOPs) are developed and examples related to skin sensitization, endocrine disruption, and mitochondrial dysfunction. Method: Narrative review based on data of the scientific literature relevant to the theme addressed and on the experience of the authors. Results: An AOP framework provides a systematic approach to organize knowledge about mechanisms of toxicity that may inform analytical domains in regulatory decision-making. AOPs are open structures that may indicate not only data gaps in the understanding of a toxicity process, but also testing procedures that will generate the necessary knowledge to fill those gaps. Every AOP should be continuously refined through the collaborative efforts of the scientific community. Depending on the amount and detail of information that is successively inserted, AOP may progress from the stage of a putative AOP to the stages of qualitative and quantitative AOPs, which are more fit-for-purpose to support regulatory decision-making. Conclusions: Continuous collaboration between AOP developers within the scientific community and the regulatory corps toward the development of this mechanistic structure will support the advancement of toxicological sciences, regardless of its immediate application for regulatory purposes.
Keywords: Adverse Outcome Pathways; Hazard Assessment; Mode of Action; Risk Assessment; Regulatory Toxicology